O cenário do rádio digital em Ribeirão Preto - Tincani, Daniela Pereira [UNESP] (2015)
The thesis aimed to present the opportunities and threats of the new scenery of digital radio in Ribeirão Preto. The research found the ways Ribeirão Preto traditional and commercial radio stations are taking advantage of the radio digitalization opportunities and analyzed the broadcasting context in the city related to national and local media conglomerates. Ribeirão Preto was selected for the research due to its pioneer past related to the radio communication development and the fact that the city provides several types of broadcasters and media groups. This research was performed from 2008 to 2014, since in 2008 was the first year of radio transmission digitalization test in the city. The development of the research was based on literature searches and interviews with the leaders of the traditional and commercial radio stations in Ribeirão Preto. The study examined aspects such as the digitalization of radio stations, new forms of interactivity with listeners and the use of other communication Medias in the digital environment. To achieve the goals, the literature helped to reflect about the digitalization of the radio as a mean of communication; about the specific regulation of this environment in Brazil; about the conglomerates and concentration of the media and also about the Internet. The results of the analysis of the interviews were confronted with the literature, what brought us to a comparative table of Ribeirão Preto stations and, from this view; we described the main opportunities and threats faced in the digital radio context studied